PRAKTIK LAPANGAN SEBAGAI UPAYA PENINGKATAN KESADARAN, PEMAHAMAN, DAN PENGALAMAN KEMARITIMAN PADA SANTRI MA UNGGULAN AL-ANWARI - Wazirotus Sakinah; Saifurridzal Saifurridzal; Nindya Nurdianasari; Selvarian Wahyu Dwi Rizky; Ilham Eka Saputra Sutrisno (Jurnal Abdi Insani, 2026)
Banyuwangi, with its extensive coastal area and long shoreline, possesses highly important yet vulnerable coastal ecosystems, particularly due to decreasing mangrove cover, increasing plastic waste, and the declining population of sea turtles. Islamic boarding schools (pesantren), as character-based educational institutions, have great potential to instill environmental awareness in younger generations. Therefore, contextual learning activities that directly engage students in coastal conservation efforts are needed. The field practice program at MA Unggulan Al-Anwari Banyuwangi was implemented as an effort to enhance students’ understanding and awareness of maritime issues and coastal conservation. The implementation method consisted of preparation, execution, and evaluation stages, involving 30 students in a series of activities including the planting of 60 mangrove seedlings and 40 sea pandan seedlings, a beach clean-up, and the release of 50 sea turtle hatchlings in the coastal area of Santen Island. The results showed that students not only gained contextual learning experiences, but were also directly involved in real actions to protect coastal ecosystems. There was an 11% increase in understanding, obtained from comparing pre-test and post-test scores. One-month post-planting monitoring showed that the seedlings remained in good condition, although height growth had not yet been significant. The average height increase of mangroves was 4.3 cm, while sea pandan showed an average increase of 3 cm within one month after planting. In addition, students consistently filled out the booklet as a recording instrument, reflecting the development of environmentally conscious habits. This program has proven effective as a pesantren-based environmental education medium while supporting the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4, SDG 13, and SDG 14.